Rheological properties of calcium sulfate suspensions. (October 2015) - Pierre, Alexandre; Lanos, Christophe; Estellé, Patrice; Perrot, Arnaud
Abstract: The rheological properties of calcium sulfate anhydrite particles dispersed in water are studied in the presence of two polycarboxylate superplasticizers. Gel permeation chromatography is used to investigate the molecular structure of the superplasticizers. Rheological shear flow measurements are carried out to investigate the effect of the two polycarboxylate superplasticizers as well as the solid volume fraction on the elastic moduli and yield stress of calcium sulfate suspensions. The affinity of polymers with calcium sulfate particles is characterized by the determination of Total Organic Carbon contents. A link is highlighted between the rheological behaviour of the suspensions, the adsorption onto mineral particles and the molecular weight of the superplasticizers. Particular attention is taken to compute the interparticle distance in the suspension as a function of the solid volume fraction and the amount of superplasticizer. For this purpose, a model based on mechanical and homogenization assumptions is developed to compute a thickness ratio of the adsorbed polymer layer. Results from the proposed model suggest that the interparticle distance is dependent on the solid volume fraction and the mix-proportion of polymer.